Gestão da idade no trabalho como mitigadora do ageísmo - Locatelli, Manoel Antonio (2025)
The main theme of this dissertation addresses age management in organizations. This topic is highlighted in various fields of study; however, it receives little emphasis in applied social sciences, particularly at the national level. Thus, researching this subject is essential due to its importance and complexity. This study seeks to analyze age management by answering the research question: how does age management contribute to mitigating ageism in the workplace? Given this question, the general objective of the study is to understand the influence of age management in mitigating ageism at work. As a breakdown of the general objective, the following specific objectives are outlined: (i) to examine how intergenerational relationships and age management practices occur in the organizations studied; (ii) to identify the presence of ageism in these organizations and how it manifests; and (iii) to assess the contribution of age management to reducing ageism in the studied organizations. This research is a single case study with an exploratory nature and a qualitative approach. The field study was conducted at Coop, a credit cooperative institution. Data were collected through structured interviews, semistructured interviews, document analysis, and non-participant observation. The collected data were organized, triangulated, and analyzed using content analysis. By applying the analytical conceptual framework supported by the Iramuteq® 0.7 software, the study concluded that age management contributes to mitigating ageism through three sets of measures: access, retention, and exit. Each group consists of different measures, which are highlighted in the data analysis. The findings contribute to advancing knowledge regarding age management in organizations. Furthermore, they underscore the importance of the organization and the Strategic People Management sector in evaluating the most effective strategies, available resources, and labor requirements to achieve positive outcomes and improve performance. The results also provide insights for future research, such as studies that relate age management to the management of other diversity markers, research that connects ageism with other forms of discrimination such as sexism, racism, and ableism and mixed-method studies.